2018
DOI: 10.1016/j.clim.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

APECED in Turkey: A case report and insights on genetic and phenotypic variability

Abstract: APECED is a rare monogenic recessive disorder caused by mutations in the AIRE gene. In this manuscript, we report a male Turkish patient with APECED syndrome who presented with chronic mucocutaneous candidiasis associated with other autoimmune manifestations developed over the years. The presence of the homozygous R257X mutation of the AIRE gene confirmed the diagnosis of APECED syndrome. We further performed literature review in 23 published Turkish APECED patients and noted that Finnish major mutation R257X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 46 publications
0
22
0
1
Order By: Relevance
“…In these independent datasets, the expanded diagnostic criteria would have also fostered a much earlier diagnosis in both American and European APECED patients and would have assisted in reaching the APECED diagnosis before development of life‐threatening endocrine complications in a significant proportion of the patients (Ferre et al, manuscript in preparation). In agreement with the potential clinical utility of these expanded diagnostic criteria, Fierabracci et al recently retrospectively analyzed previously reported APECED cohorts from Finland, Sardinia, and Turkey and showed that the application of these expanded diagnostic criteria would have also allowed for earlier recognition and diagnosis in these APECED patients. Collectively, these findings indicate that children with APECED are as likely or even more likely to be seen early in the course of their disease by dermatologists, allergists, dentists, hepatologists, pulmonologists, ophthalmologists, and/or gastroenterologists than by endocrinologists.…”
Section: Diagnosis Of the Suspected Apeced Patientmentioning
confidence: 75%
See 1 more Smart Citation
“…In these independent datasets, the expanded diagnostic criteria would have also fostered a much earlier diagnosis in both American and European APECED patients and would have assisted in reaching the APECED diagnosis before development of life‐threatening endocrine complications in a significant proportion of the patients (Ferre et al, manuscript in preparation). In agreement with the potential clinical utility of these expanded diagnostic criteria, Fierabracci et al recently retrospectively analyzed previously reported APECED cohorts from Finland, Sardinia, and Turkey and showed that the application of these expanded diagnostic criteria would have also allowed for earlier recognition and diagnosis in these APECED patients. Collectively, these findings indicate that children with APECED are as likely or even more likely to be seen early in the course of their disease by dermatologists, allergists, dentists, hepatologists, pulmonologists, ophthalmologists, and/or gastroenterologists than by endocrinologists.…”
Section: Diagnosis Of the Suspected Apeced Patientmentioning
confidence: 75%
“… Shown are approximate percentages of corresponding APECED manifestations pooled from various published studies comparing data from the American or other international cohorts …”
Section: Diagnosis Of the Suspected Apeced Patientmentioning
confidence: 99%
“…Other homozygous mutations were reported in patients with defects in the MEFV and AIRE genes, and known for the hot-spot mutations. (35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…In Table 2, the prevalence of AAD and APOI in various APS1 patient cohorts is reported, with the specification of their ethnic backgrounds (15,144,153,(181)(182)(183)(184)(185)(186)(187)(188)(189)(190)(191)(192)(193)(194)(195)(196)(197). AAD prevalence can sometimes be influenced by the mean patient age, for example, in Saudi patients with APS1 described by Bin-Abbas et al (193).…”
Section: Prevalence Of Aps1-associated Aad and Apoimentioning
confidence: 99%